Drought-Tolerance Gene Identification Using Genome Comparison and Co-Expression Network Analysis of Chromosome Substitution Lines in Rice - Punchkhon, Chutarat; Plaimas, Kitiporn; Buaboocha, Teerapong; Siangliw, Jonaliza L; Toojinda, Theerayut; Comai, Luca; De Diego, Nuria; Spíchal, Lukáš; Chadchawan, Supachitra (Genes, 2020)
Drought stress limits plant growth and productivity. It triggers many responses by inducing changes in plant morphology and physiology. KDML105 rice is a key rice variety in Thailand and is normally grown in the northeastern part of the country. The chromosome segment substitution lines (CSSLs) were developed by transferring putative drought tolerance loci (QTLs) on chromosome 1, 3, 4, 8, or 9 into the KDML105 rice genome. CSSL104 is a drought-tolerant line with higher net photosynthesis and leaf water potential than KDML105 rice. The analysis of CSSL104 gene regulation identified the loci associated with these traits via gene co-expression network analysis. Most of the predicted genes are involved in the photosynthesis process. These genes are also conserved in Arabidopsis thaliana. Seven genes encoding chloroplast proteins were selected for further analysis through characterization of Arabidopsis tagged mutants. The response of these mutants to drought stress was analyzed daily for seven days after treatment by scoring green tissue areas via the PlantScreen™ XYZ system. Mutation of these genes affected green areas of the plant and stability index under drought stress, suggesting their involvement in drought tolerance.
Keywords: CSSLs; Adaptation, Physiological; Droughts; Gene Regulatory Networks; stanovení celkové genové exprese; fyziologická adaptace; rostlinné proteiny; chromozomy rostlin; Chromosomes, Plant; regulace genové exprese u rostlin; Gene Expression Profiling; ‘KDML105’ rice; lokus kvantitativního znaku; Oryza; genové regulační sítě; drought stress; Gene Expression Regulation, Plant; rýže (rod); Quantitative Trait Loci; co-expression network; období sucha; Plant Proteins